Implementasi Metode Class Based Storage dalam Penempatan Bahan Baku di PT XYZ Bandung - I Kadek Hendra Sumerta Dana; Nenden Kostini (Jurnal Sekretaris dan Administrasi Bisnis, 2024)
This research aims to optimize the layout of raw material storage by reducing the distance needed to take the required raw materials, random placement of raw materials results in the raw material storage layout being less effective. This research was conducted for three months from August to November by means of observations and interviews with related parties. It is proven that the implementation of the Class Based Storage method can be a solution in structuring raw material warehouses which can provide significant benefits in terms of efficiency and better management of raw materials seen from the frequency of movement of goods before implementing the class based storage method, namely reaching 21,911 meters and after implementation. the frequency of movement distances is 14,691 meters, which shows that there is a decrease in the distance required for collecting raw materials, which indicates the effectiveness of implementing the class based storage method.